In response to disruption: how and why companies should carefully assess their strategy towards new technologies - Birkinshaw, Julian (Henry Stewart Talks, 2023)
Assessing new technologies, The hype cycle, Blockchain, The killer app, Strategy, Trends, Pivoting, Autonomous electric vehicles